A nova direita no Brasil (2011-2016): uma análise da atuação política no facebook - Grassiolli, Isabel (2019)
This research carried out a study about the fascistization process experienced in Brazil in the period from 2011 to 2016. For this, we propose to analyze a set of Facebook pages on the internet, characterized by a political profile of groups that call themselves right-wing, liberals, defenders of private property, defenders of free enterprise, and, in some cases, they call themselves reactionaries. The groupings investigated here were widely known on social networks on the internet for an alleged non-partisan militancy that brought together an anti-corruption movement, driven by a common ideological component: antipetismo, a term used to describe an ideology against the Brazilian Workers’ Party (PT), and the need to prevent the implementation of communism in Brazil and Latin America, which, according to the online channels of the Brazilian New Right, was being promoted, in a particular way, by Lula (Luiz Inácio Lula da Silva) and PT. The criteria for choosing the pages are related first to their programmatic content. We try to present here a set of ultra-conservative and anti-communist Facebook pages. Part of their agenda defends the minimal state, the reduction of the age of criminal responsibility, the death penalty, the possession of weapons, the prevention of what they call “gayism” (which, according to its promoters, would be the imposition of the “homosexual way of life on society”), and the fight against public policies such as the financial aid called Bolsa Família and the quotas for black people, as they believe that these measures make people too “laid-back.” Our working hypothesis suggests that the reactionary social phenomenon experienced in Brazil at the moment directly intertwines with the massification of social networks on the internet, of which we highlight the hegemonic role of Facebook in this process. We believe that this performance, via the World Wide Web, constitutes a new organizational possibility, where the Internet appears as being an “instrument” that enhances the partisan action of these groups in contemporary times. When thinking about the influence that social networks on the Internet have on reality, we seek to reflect on the role played by the ideology and the emotional attitude of the masses as a historical factor. For that, we seek to base our analyses through mass psychology and try to understand the modes of subjectivity corresponding to specific social and political configurations of our time.